2017
DOI: 10.1055/s-0037-1606349
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 Levels in Recurrent Implantation Failure

Abstract: Sirtuin 1 has an important role in cellular processes, including apoptosis and cellular stress. The purpose of this study was to assess serum sirtuin 1 levels in women with recurrent implantation failure (RIF). In this cross-sectional study, we included 28 women with RIF, 29 healthy women who had conceived by in vitro fertilization (IVF), and 30 women with a 1-cycle failure of IVF as controls. Human serum nicotinamide adenine dinucleotide (NAD)-dependent deacetylase sirtuin-1 (SIRT1/SIRT2L1) levels were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While LPS and the inflammatory cytokines TNF-α and IL-1β negatively regulate the mRNA expression of SIRT1, SIRT2 expression level may be regulated by a mechanism independent of inflammation in the human placenta [20]. Women suffering from recurrent implantation failure (RIF) are reported to have higher levels of SIRT1 in their serum as compared to non-pregnant women and healthy pregnant women; however, it should be mentioned that this report may show poor reproducibility due to the low number of subjects [87]. Importantly, the expression patterns of local and systemic cytokines are markedly changed in patients with RIF.…”
Section: Correlation Between Proinflammatory Cytokines and Sirtuin Le...mentioning
confidence: 86%
“…While LPS and the inflammatory cytokines TNF-α and IL-1β negatively regulate the mRNA expression of SIRT1, SIRT2 expression level may be regulated by a mechanism independent of inflammation in the human placenta [20]. Women suffering from recurrent implantation failure (RIF) are reported to have higher levels of SIRT1 in their serum as compared to non-pregnant women and healthy pregnant women; however, it should be mentioned that this report may show poor reproducibility due to the low number of subjects [87]. Importantly, the expression patterns of local and systemic cytokines are markedly changed in patients with RIF.…”
Section: Correlation Between Proinflammatory Cytokines and Sirtuin Le...mentioning
confidence: 86%
“…McBurney et al (2003) found for the first time that SIRT1 null mice are characterized with thin-walled uterus, suggesting that SIRT1 might play an important role in endometrial functions. A study showed RIF patients have higher SIRT1 levels than healthy pregnant women in serum during the 1st to 3rd days of the menstrual cycle, but no statistical significance (Engin-Ustun et al, 2017). However, the abundance of SIRT1 might be different between serum and local endometrial concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sirtuin 1 ( SIRT1 ), a gene that plays a crucial role in necroptosis, has been reported to be significantly upregulated in RIF. [ 7 9 ] Additionally, levels of cell-derived microparticles (cMPs), released during cell activation or apoptosis, are found to increase significantly in RIF patients. [ 10 ] Moreover, trophoblast necroptosis plays a complex role in pregnancy disorders such as preeclampsia [ 11 , 12 ] and recurrent abortion.…”
Section: Introductionmentioning
confidence: 99%